Current Rehabilitation Practices of Physiotherapists in Intensive Care Units in the UAE: A National Survey [version 1; peer review: 2 approved, 1 not approved] - Kalyana Chakravarthy Bairapareddy; Amira Hassan Bekhet; Emad A. Aboelnasr; Gopala Krishna Alaparthi; Monia Ashraf Megahed; Fatma A. Hegazy; Alham Al-Sharman; Heba Hijazi (F1000Research)
Abstract* Background Intensive care units (ICUs) are essential for patient recovery, but prolonged stays often result in complications like reduced mobility and muscle weakness. Aims This study examines current ICU rehabilitation practices in the United Arab Emirates (UAE) through a web-based cross-sectional survey involving 80 physiotherapists from both public and private sectors. Methods The questionnaire, validated by experts with a Cronbach’s alpha of 0.84, explored various rehabilitation strategies. Most participants held bachelor’s degrees and had 2-5 years of experience. Results Over 96% required physician referrals for ICU physiotherapy sessions, and 75% noted that hospitals provided development programs to enhance skills. Respiratory therapy, joint mobilization, and electrical stimulation were the most commonly used interventions, while massage, continuous passive motion machines, and taping were less frequently applied. Among neonatal ICU patients, 85.7% of physiotherapists regularly performed passive range of motion exercises, and 69% consistently involved parents in the treatment plan. The results indicate a variety of practices among ICU physiotherapists in the UAE, with no clear adherence to standardized protocols. This lack of consistency may negatively affect patient care quality. Conclusion The study underscores the importance of implementing standardized rehabilitation protocols and enhancing patient education to improve outcomes in ICU settings.